Harnessing the synergy of Urochloa brizantha and Amazonian Dark Earth microbiomes for enhanced pasture recovery. - FREITAS, A. S. de (2025)
Amazonian Dark Earths (ADEs) are fertile soils from the Amazon rainforest that harbor microorganisms with biotechnological potential. This study aimed to investigate the individual and potential synergistic effects of a 2% portion of ADEs and Urochloa brizantha cv. Marandu roots (Brazil’s most common grass species used for pastures) on soil prokaryotic communities and overall soil attributes in degraded soil. We conducted a comprehensive plant succession experiment in the greenhouse, utilizing vase soil samples for next-generation sequencing of 16 S rDNA, enzymatic activity assays, and soil chemical properties analysis. Univariate and multivariate analyses were performed to understand better the prokaryotic interactions within soil environments influenced by ADEs and U. brizantha roots, including differential abundance, diversity, and network analyses. Our findings reveal a complementary relationship between U. brizantha and ADEs, each contributing to distinct positive aspects of soil bacterial communities and quality. The combined influence of U. brizantha roots and ADEs exhibited synergies that enhanced prokaryotic diversity and enzyme activity. This balance supported plant growth and increased the general availability of beneficial bacteria in the soil, such as Chujaibacter and Curtobacterium while reducing the presence of potentially pathogenic taxa. This research provided valuable insights into the intricate dynamics of plant-soil feedback, emphasizing the potential for complementary interactions between specific plant species and unique soil environments like ADEs. The findings highlight the potential for pasture ecological rehabilitation and underscore the benefits of integrating plant and soil management strategies to optimize soil characteristics.